DEVELOPMENT OF YAKUT FIGURATIVE VERBSDESCRIBING PERSON’S WALK (COMPARED TO MONGOLIAN PARALLELS) - Shamaeva, Anastasia; Monastyrev, Vladimir (Revista Inclusiones, 2020)
The paper deals with ways of semantic change in Yakut figurative verbs describing person’s walk in comparison with their Mongolian parallels. A total of 11 stems describing walk of human and animals are analyzed. No fully identical stems have been found. It shows that each Yakut figurative verb describing person’s walk in some degree demonstrates semantic change. The present paper continues a series of research papers elaborating on the category of figurativeness in Yakut in comparison with Mongolian. Figurative verbs are the most vivid and expressive part of Yakut vocabulary but, unfortunately, they gradually go out of use. As compared to other Turkic languages they make up a large layer of vocabulary which is characterized by specific semantics. They are present only in those Turkic languages that were significantly influenced by Mongolian. To clarify the historical development of the Yakut language it is necessary to study contacts between Yakut and Mongolian. The illustrative material was taken from the Great Explanatory Dictionary of the Yakut Language edited by P. A. Sleptsov, Learner’s Dictionary of Yakut Figurative Verbs, and the four-volume Great Academic Mongolian-Russian Dictionary edited by A. Luvsendendeva. The illustrative lexical material compared with Mongolian showed that Yakut figurative verbs describing person’s walk were based on the following waysof semantic change: narrowing of the semantic content of the word, association based on similarity (similarity in appearance of the compared subjects), and semantic derivation.